Structures, functions and flows of IWT: deconstructing a criminal network between East Africa and Southeast Asia - Costa, Jacopo (Crime, law and social change, 2022)
The paper investigates the role of criminal networks in fostering illegal wildlife trade (IWT), and how these relational structures interact with transnational organized crime. The paper frames these topics within the debate around the opportunistic or organized nature of IWT. The aim is to understand how chaotic behaviors can transform into an ordered and organized strategy. Social network analysis (SNA) and network ethnography were conducted to explore the crime network surrounding a wildlife trafficker based in East Africa. The empirical results suggest that criminal networks operate as "machine of order" that transform opportunistic behaviors at the micro level into ordered strategies at the macro level. Empirical results also suggest that organized crime has an important role in making the process of transforming opportunistic into organized behaviours more efficient and more effective.